EFL teachers' perceptions toward using artificial intelligence (AI) in English teaching practice at a private language institute in Loja, cycle February - June 2024 - Guerrero Ayora, Steven Eduardo (2024)
This research aimed to identify EFL teachers' perceptions of integrating artificial intelligence (AI) in their English teaching practices, inquire how these teachers incorporate AI technologies, and describe the challenges they face. To accomplish these aims, a mixed-methods approach was employed, combining a survey technique with a questionnaire completed by 42 EFL teachers and semi-structured interviews with five teachers using an open-ended questionnaire. Subsequently, data analysis involved descriptive statistics and thematic analysis. The findings indicate that teachers generally view AI as beneficial for personalized learning, student engagement and workload reduction. Similarly, ethical concerns such as data privacy and the use of AI-generated content were expressed. The study revealed that teachers use various AI tools, with Chat GPT being the most common, followed by Grammarly, ELSA Speak, and Canva. In spite of facing several challenges, including infrastructure issues, reliability concerns, and ethical considerations such as potential plagiarism, the outlook among teachers remains cautiously optimistic. Consequently, the study suggests that while AI integration in EFL teaching can enhance learning outcomes, it also requires a special focus on teacher training, infrastructure development, and the establishment of ethical guidelines to effectively address concerns and maximize its potential. Keywords: AI integration in education, AI uses in language teaching, Language teaching innovation.